Statistical inference and optimum life-testing plans with joint progressively type-II censoring scheme. Issue 3 (4th May 2023) - Lin, Chien-Tai; Chen, Yen-Chou; Yeh, Tzu-Chi; Ng, Hon Keung Tony
ABSTRACT: This article discusses the estimation of model parameters and the determination of optimal life-testing plans for Weibull-distributed lifetimes under a joint progressive Type-II censoring scheme. We obtain the maximum likelihood estimates numerically and propose a modified variable-neighborhood-search-based approach for determining the optimum joint progressive Type-II censoring scheme. Different optimal criteria, including a cost minimization criterion, the A -optimality criterion, and the D -optimality criterion, are considered. A sensitivity analysis is used to study the effect of misspecification of parameter values on the optimal schemes.